Improving the TiO2 electron transport layer in perovskite solar cells using acetylacetonate-based additives1. Issue 17 (7th May 2015) - Wang, Hsin-Hua; Chen, Qi; Zhou, Huanping; Song, Luo; Louis, Zac St; Marco, Nicholas De; Fang, Yihao; Sun, Pengyu; Song, Tze-Bin; Chen, Huajun; Yang, Yang
<x xml:space="preserve">Abstract</x> A facile and quantitative approach has been demonstrated to improve the TiO2 ETL in perovskite solar cells, with enhanced carrier extraction.